Digital Literacy, Electronic Word Of Mouth Dan Strategi Social Media Marketing Terhadap Peningkatan Penjualan Umkm Kota Sungai Penuh - Melifia Liantifa; Cinta Amelia; Alvia Santoni, Anggia Ayu Lestari (YUME : Journal of Management, 2026)
This study aims to determine the influence of Digital Literacy, Electronic Word of Mouth (E-WOM), and Social Media Marketing on sales improvement of MSMEs, with a case study on CN Store. The research employs a quantitative method with purposive sampling, involving 90 consumer respondents. Data analysis techniques include multiple linear regression, t-test, F-test, and the coefficient of determination. The results show that Digital Literacy does not have a significant partial effect on sales improvement (significance value 0.407 > 0.05). E-WOM has a positive and significant effect and is identified as the most dominant variable (significance value 0.000 < 0.05). Social Media Marketing also does not have a significant partial effect on sales improvement (significance value 0.257 > 0.05). Simultaneously, the three variables significantly influence sales improvement, indicated by an F-value of 37.609 with a significance level of 0.000 < 0.05. The determination coefficient (R Square) of 0.567 indicates that 56.7% of the variation in sales improvement is explained by the independent variables, while the remaining 43.3% is influenced by other factors.